Ocena skutków regulacji jako narzędzie poprawy jakości stanowienia prawa w Polsce - Bramorski, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The efficiency of the legislative process and the quality of polish legal acts, raise serious reservations. The system solutions that could erase those deficits are missing. An undervalued and not being used appropriately tool that could improve the situation is the regulatory impact assessment (RIA), especially the assessment of the effects. The current position of RIA in the legal sources system and the content of its provisions are the reasons of the fragmentation of its application in the process of legislation and the descent of its diagnostic value from the perspective of the legislator. The observations of international standards and the good legislation practice, implemented in other EU countries, permit the conclusions that provide a basis for improvement of the quality of statutory law through the expansion of the content and the scope of application of RIA. The suggested changes are aiming especially for the dissemination of RIA through the extension of the obligation of preparing RIA for all the legislative initiatives, updating it throughout the process of legislation and establishing a body to control the correctness and reliability of RIA’s drafting.
Keywords: legislation; good legislation; the legislative process